Effects of non-pharmacological interventions on cognitive function in patients with type 2 diabetes mellitus and mild cognitive impairment: A network meta-analysis - Wenzhuo An; Dongqing Guo; Jie Wang; Xin Chu (PLoS ONE, 2025)
Objective Non-pharmacological intervention represents a significant therapeutic modality for the cognitive function intervention management of patients with type 2 diabetes accompanied by mild cognitive impairment. However, it remains unclear which intervention measure is the most effective. The objective of this study is to compare and rank the influences of various non-pharmacological interventions on the cognitive function of patients with type 2 diabetes and mild cognitive impairment. Methods Eight databases from the establishment of the database to November 2024 were retrieved. The quality of the literature was evaluated using the RoB2.0 tool. Paired Meta-analysis was conducted using Stata/SE 15.1 software, and Network Meta-analysis was performed using R 4.3.1 software. Results A total of 25 literatures were incorporated, encompassing 5 intervention measures, with a sample size of 2,446 cases. The results indicated that in the pairwise meta-analysis, when the MoCA score was used as the outcome indicator, cognitive training [MD = 2.3, 95% CI (1.64, 2.96), P < 0.01], exercise therapy [MD = 2.11, 95% CI (1.30, 2.92), P < 0.01], TCM therapy [MD = 2.28, 95% CI (0.76, 3.81), P < 0.01], and comprehensive intervention [MD = 1.98, 95% CI (1.53, 2.48), P < 0.01] were more effective in improving the cognitive status of patients than the control group; when the MMSE was used as the outcome indicator, cognitive training [MD = 2.03 95% CI (1.57, 2.49), P < 0.01], exercise therapy [MD = 2.78, 95% CI (1.48, 4.08), P < 0.01], and TCM therapy [MD = 2.09, 95% CI (1.46, 2.73), P < 0.01] were more effective in improving the cognitive status of patients than the control group. The SUCRA ranking revealed that in terms of improving the MoCA scores, the comprehensive intervention (SUCRA 76.9%), cognitive training (SUCRA 63.3%), and TCM therapy (SUCRA 57.9%) were the top 3 preferred treatment measures; for improving the MMSE scores, exercise therapy (SUCRA 78.0%) and cognitive training (SUCRA 73.8%) were the preferred treatment measures. Conclusion The current evidence indicates that cognitive training, exercise therapy, and TCM therapy might be relatively effective intervention approaches for improving the cognitive function of patients with type 2 diabetes mellitus (T2DM) accompanied by mild cognitive impairment (MCI), and cognitive training could potentially be the most efficacious non-pharmacological treatment method. Constrained by the quantity and quality of the studies, more high-quality research is still required in the future to further validate this conclusion.